Mutagenic and antimutagenic evaluation of Asparagus laricinus Burch., Senecio asperulus DC., and Gunnera perpensa L. to hepatic cells - Mfengwana, Polo-Ma-Abiele Hildah (Journal of Medical Science, 2022)
Introduction. The use of traditional medicinal plant concoctions to cure or treat different diseases daily in African folk medicine. However, the effects of most medicinal plants on human health or genetic material remain unknown. This study thus aimed to evaluate the mutagenic and antimutagenic potentials of Asparagus laricinus Burch. cladodes, Senecio asperulus DC., and Gunnera perpensa L. roots extract in vitro. Material and methods. Neutral red uptake assay, alkaline comet assay, and the VITOTOX test was used with plant extract dilutions of 4, 20, 50, and 100 µg/ml, respectively, on hepatic (C3A) cells and Salmonella Typhimurium TA104 strains. Ethyl methane-sulfonate and 4-nitroquinoline oxide were used as positive controls for the comet and VITOTOX assays, respectively. Results. In vitro cytotoxicity and genotoxicity were not observed from all tested extracts, except for the two dichloromethane (DCM) extracts of S. asperulus and G. perpensa, which appeared to be cytotoxic with S9 metabolic activation, but not genotoxic or mutagenic. From the VITOTOX test results, none of the extracts appeared to have antimutagenic properties after treating S. Typhimurium strains with a known mutagen. Conclusions. These results confirm that previously reported anticarcinogenic properties of A. laricinus, S. asperulus, and G. perpensa did not result from the protective mechanism against genotoxicity but from other ones. Moreover, the negative mutagenic and cytotoxic activities of the tested plants highlighted the safe use of these medicinal plants in vitro. Therefore, S. asperulus and G. perpensa DCM extracts require further investigation for their possible in vivo cytotoxic effects on humans.